THE INFLUENCE OF LEADERSHIP STYLE ON EMPLOYEE WORK MOTIVATION AT PT. PAWNSHOP (PERSERO) PANAM PEKANBARU BRANCH - Aprilia Anjelly; Nurman (Proceeding International Conference on Social Sciences, 2026)
Leadership has an important role in encouraging employee enthusiasm and performance so that the company's goals can be achieved with full integrity and trust for the common good. The leadership style applied by a leader can affect employee productivity, loyalty, and work motivation. PT. Pegadaian (Persero) Panam Pekanbaru Branch as a financial services company engaged in financing requires an effective leadership style to keep employees' work motivation optimal. This study aims to determine the influence of leadership style on employee work motivation at PT. Pegadaian (Persero) Panam Pekanbaru Branch. According to Thoha (2015:303), leadership style is a pattern of behavior applied by a person when trying to influence the actions or behavior of others according to their perception. Meanwhile, according to Sutrisno (2009:110), motivation is the result of interaction between individuals and certain situations, thus causing differences in motivational strength among individuals. This study uses a quantitative approach with a saturated sampling method, involving all 31 employees. The data analysis technique used SPSS version 27 through validity, reliability, simple linear regression, t-test, and determination coefficient (R²). The results showed that leadership style had a positive and significant effect on employee work motivation, with an R² value of 0.683 or 68.3%. It is suggested that the transactional leadership style applied continues to be improved with a balance between reward and supervision, as well as combined with a humanist and communicative approach.